Total quality management and competitive advantage affect company performance - Andini, Erfiannur Diani Rifkha; Syamsudin, Achmad; Harjoni, Harjoni (JSM: Jurnal Sains Manajemen, 2024)
This study aims to determine whether there is a significant effect between Total Quality Management and competitive advantage on company performance. The TQM variable is measured from eight indicators: Top Management Support, Quality Information, Process Management, Product Design, Workforce Management, Supplier Involvement, Customer involvement, and Employee Empowerment. The competitive advantage variable is measured from five indicators: price, quality, delivery dependability, product innovation, and time to market. The company's performance variable will be calculated from two indicators, namely financial performance and operational performance. Data was collected using observation, interviews, and distributing questionnaires. The unit of research analysis is PT Bank Kalteng in Palangka Raya. Respondents who were used as samples were 30 people. The analytical method used in testing the hypothesis is a multiple linear regression test. This study proved a significant relationship between Total Quality Management and competitive advantage on company performance, Total Quality Management on company performance, and competitive advantage on company performance